(untitled) (Archives of Criminology, 2023)
In the beginning of the 21st century, a day labourer market was established in the southern main station district of Munich. In August 2013, the market aroused negative public attention due to a petition from local businesspeople. Since then, the day labourers have been subject to surveillance and banishment. In 2019, a significant amendment to the Illegal Employment Act made day labourer markets illegal. It is known that day labourers offer their own labour to employers, who frequently deprive them of the agreed wage. This practice poses the question of whether these exploitative working conditions amount to human trafficking, forced labour, or labour exploitation. This question is explored in a case study analysis based on talks with day labourers and interviews with different actors in Munich’s train station district.